New species of Phenacorhamdia (Siluriformes: Heptapteridae) from the Xingu River basin - Silva,Gabriel S. C. (2022)
Abstract Heptapteridae is a diverse group of catfishes composed of 231 valid species endemic to the Neotropical region, recognized in two subfamilies: Rhamdiinae and Heptapterinae. Phenacorhamdia is a Heptapterinae member and currently has 13 valid species broadly distributed throughout the main river basins of South America. Here we described a new species of Phenacorhamdia from the Xingu River basin. Morphological data were obtained from 30 specimens under 23 morphometric measures and 6 meristic counts. The new species differs from congeners based on the exclusive combination of the following diagnostic characters: atypical mottled colored body and all fins with interradial membranes mottled pigmented; multicuspid teeth; maxillary barbel reaching pectoral-fin origin; lacking a short extension of the first pectoral-fin ray; caudal fin lobes extremely elongated and pointed; and 43−45 total vertebrae.